Kinship and association do not explain vocal repertoire variation among individual sperm whales or social units. (November 2018) - Konrad, Christine M.; Frasier, Timothy R.; Rendell, Luke; Whitehead, Hal; Gero, Shane
Abstract : Vocal learning often results in distinct dialects among individuals or groups, but the forces selecting for these phenomena remain unclear. Female sperm whales, Physeter macrocephalus, and their dependent offspring live in matrilineally based social units, and the units associate within sympatric clans. The clans have distinctive dialects of codas (patterns of clicks), as do, to a lesser extent, the units within clans. We examined the similarity of coda repertoires of individuals and units from the eastern Caribbean and related these to patterns of kinship and social association. Similarity in coda repertoires was not discernibly correlated with close kinship or association rates for either individuals or units (matrix correlation coefficients <0.12 for all tests using whole repertoires and data from all units). This supports the prevailing hypothesis that these vocalizations are culturally transmitted. The lack of correlation also indicates that vocal learning may occur broadly within clans, rather than preferentially from close kin or close social associates within social units, or that biases in vocal learning at lower levels of social structure are diffused by clan-level processes, such as conformity. Finally, an absence of signals of kinship in vocalization patterns suggests that a different mechanism, perhaps familiarity through repeated association, mediates kin selection among sperm whales. Highlights: In social units of sperm whales, close kin do not have similar vocal dialects. In social units of sperm whales, close associates do not have similar vocal dialects. Closely kin-related social units do not have similar dialects. Social units that often associate do not have similar dialects. Clans have very different vocal dialects, but there may be kinship across clans.